Nos passos do capitalismo: estratégias de reestruturação produtiva da indústria calçadista no nordeste brasileiro - Moura, Bruna Mariana Oliveira dos Santos (2020)
Given the growing movement for productive restructuring that has plagued the world of work since 1970, what are the consequences for the footwear industry and, above all, how has this been manifesting in "peripheral regions" such as the Brazilian Northeast? The answer to this question supposes the treatment of the theme from the analysis of the capitalist systemic contradiction, a path that the present research followed whose object of study was the process of productive restructuring in the footwear sector in the Northeast region, in the period 2008 to 2018. The objective was to analyze the main strategies adopted by the sector in the region in question to understand the process of productive restructuring. The specific objectives were defined: a) to understand the theoretical and historical determinants of the post-1970 crisis of capitalism; b) to outline a historical panorama of the Brazilian industry, with emphasis on the footwear sector; c) to identify the main productive restructuring strategies in the Brazilian footwear industry, especially in the Northeast. The study started from two guiding premises, namely: 1) In the context of a contraction in the production of material goods and an increase in income from fictitious capital (which represents a reduction in jobs), workers have been suffering greater refractions from the precarious work movement and in the context of third world countries, this dimension is accentuated; 2) The existence of a hybrid model in the footwear industry - with characteristics of the Fordist / Taylorist accumulation pattern and features of flexible accumulation –, leads to different forms of exploitation and precarious work. Based on historical dialectical materialism, the research was characterized by an exploratory-descriptive-analytical qualitative approach, of a bibliographic type. The data content to extract the research inputs was taken from the Brazilian Digital Library of Theses and Dissertations (BDTD) of the Coordination for the Improvement of Higher Education Personnel (CAPES). The data universe was collected in the works produced on the Northeastern footwear sector in the period from 2008 to 2018; sampling was defined by applying filters as to: the area of knowledge, area of concentration, type of work (dissertations). From probing readings of keywords, titles, abstracts and abstracts of the dissertations, the glossed works were completely defined that generated the synthesis of the dissertation. Nine dissertations from different areas of knowledge were selected and analyzed in their entirety. The research unit showed itself in the signal that the main changes for the footwear industry have in fact occurred since 1990 and that these changes were based on the productive restructuring and its various mechanisms. The particularities were widely found, each author adopted a different mechanism to go deeper, according to their objectives. Technological innovations were a consensus among the works, but it was possible to observe that each author (despite admitting the totality of productive restructuring: technological / organizational innovation, spatial restructuring / cheap labor) found a factor as the most effective for the super profit of the industries. Two of the works claim that the center of profit is the potential for exploiting northeastern labor, another three admit that this migration is linked to the State's fiscal concessions; for three other authors, everything depends on the technological advancement and organizational structure of each company.